2016
DOI: 10.1021/acs.jproteome.6b00604
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Proteomics Analysis Reveals Metabolic Reprogramming of Tumor-Associated Macrophages Stimulated by the Tumor Microenvironment

Abstract: Tumor-associated macrophages (TAMs) are major components of the tumor microenvironment. Although a role for TAMs in promoting tumor progression has been revealed, the differentiation mechanisms and intrinsic signals of TAMs regulated by the tumor microenvironment remain unclear. Here we constructed an in vitro TAMs cell model, TES-TAMs, which is from tumor-extract-stimulated bone-marrow-derived macrophages. We performed a comparative proteomics analysis of bone-marrow-derived macrophages and TES-TAMs, which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
72
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 56 publications
11
72
1
1
Order By: Relevance
“…In line with previous studies [28], TES-TAMs displayed a mixture of a M1/M2 phenotype, characterized by upregulation of proinflammatory cytokine and chemokine genes, while ARG1, IL4Ra and perilipin-2 (PLIN2), which is involved in the formation of lipid droplets and associated with M2 macrophages, were also upregulated [75].…”
Section: Glucose Metabolism In Tamssupporting
confidence: 90%
See 2 more Smart Citations
“…In line with previous studies [28], TES-TAMs displayed a mixture of a M1/M2 phenotype, characterized by upregulation of proinflammatory cytokine and chemokine genes, while ARG1, IL4Ra and perilipin-2 (PLIN2), which is involved in the formation of lipid droplets and associated with M2 macrophages, were also upregulated [75].…”
Section: Glucose Metabolism In Tamssupporting
confidence: 90%
“…performed a comprehensive proteomics analysis to study the metabolic reprogramming of murine tumor‐extract‐stimulated bone‐marrow‐derived macrophages (TES‐TAMs), in which they unraveled that aerobic glycolysis was increased in TAMs compared with bone‐marrow‐derived macrophages (BMDMs). Hexokinase‐2 (HK2), a key mediator of aerobic glycolysis, and the expression of downstream proteins phosphofructokinase and enolase 1 (ENO1) was increased in TES‐TAMs and primary TAMs from their mice model, as well as human THP‐1 cell lines stimulated by tumor extract solution . In line with previous studies , TES‐TAMs displayed a mixture of a M1/M2 phenotype, characterized by upregulation of proinflammatory cytokine and chemokine genes, while ARG1, IL4Rα and perilipin‐2 (PLIN2), which is involved in the formation of lipid droplets and associated with M2 macrophages, were also upregulated .…”
Section: Glucose Metabolismsupporting
confidence: 85%
See 1 more Smart Citation
“…In the MCT4 −/− animals, the number of macrophages noted in the tumor microenvironment is lower compared to the wild type (Figure 6M) suggesting that MCT4 in either one of the compartments, or in both of them, has an effect on the macrophage population. MCT4 is usually associated with a higher glycolytic flux, therefore TAMs may have a glycolytic metabolism as suggested by Liu et al (43). It has also been reported that bone marrow derived macrophages (BMDM) knock down of MCT4 reduced the production of cytokines after LPS stimulation (12), indicating that the F4/80 cells in the tumor microenvironment of the MCT4 −/− animals may be compromised.…”
Section: Discussionmentioning
confidence: 89%
“…Indeed, in a thyroid carcinoma model, tumor‐conditioned macrophages were shown to display a glycolytic phenotype which correlated with their inflammatory and pro‐tumor phenotype . Similarly, proteomic analysis of TAMs in a breast cancer model, also reported the upregulation of several glycolysis‐related proteins, suggestive of a glycolytic phenotype of these cells …”
Section: Metabolic Control Of Macrophages In Cancermentioning
confidence: 89%